Fixed point theorems for generalized Lipschitzian semigroups in Banach spaces - Balwant Singh Thakur; Jong Soo Jung (International Journal of Mathematics and Mathematical Sciences)
Fixed point theorems for generalized Lipschitzian semigroups are proved in p-uniformly convex Banach spaces and in uniformly convex Banach spaces. As applications, its corollaries are given in a Hilbert space, in Lp spaces, in Hardy space Hp, and in Sobolev spaces Hk,p, for 1<p<∞ and k≥0.